2022
DOI: 10.1038/s41598-021-04530-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of syphilis in pregnant women and congenital syphilis in the state of São Paulo, Brazil

Abstract: We aimed to estimate the occurrence of syphilis in pregnant women (SPW) and congenital syphilis (CS) in the municipalities of the state of São Paulo (SP) and evaluate their relationship with socioeconomic, demographic, and health care variables. We developed an ecological study based on secondary data of SPW and CS with spatiotemporal components from 645 municipalities in SP including data from 2007 to 2018. We modeled the data in a Bayesian context, considered spatial and temporal random effects, and used bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
4
0
5
Order By: Relevance
“…Our analysis corroborates studies that show a relationship between the prevalence of syphilis and municipalities with higher demographic densities, because they show social and health determinants that enable the dissemination of the infection and, despite offering a wider health care service, it maintains social disparities and the populations’ difficulties to access the services [ 5 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our analysis corroborates studies that show a relationship between the prevalence of syphilis and municipalities with higher demographic densities, because they show social and health determinants that enable the dissemination of the infection and, despite offering a wider health care service, it maintains social disparities and the populations’ difficulties to access the services [ 5 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Potential factors that have likely contributed to increasing infectious syphilis cases and the re-emergence of congenital syphilis in higher income countries include an increase in high-risk sexual activities (multiple partners, overlapping relationships, sexual gender fluidity, drugs, alcohol and chemsex), increased travel and migration [17,19,21,22 ▪▪ ,23], factors that limit access to antenatal care (social and economic changes, closure of sexual health clinics, COVID-19, income loss and increased numbers of marginalized young women) and limited awareness and education amongst mothers and maternity services [8 ▪▪ ,16 ▪ ,17,19,21,22 ▪▪ ,23,24,25 ▪ ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The present study identified spatial clusters of municipalities with high rates of CS and SiP in Brazil. Between 2001 and 2017, almost all regions and microregions of the country reported a higher intensity of CS and SiP infections [ 47 , 54 , 57 – 62 ]. However, in most of Brazil’s microregions, there are few studies of these regions that do not highlight these areas as priority for a syphilis surveillance study.…”
Section: Discussionmentioning
confidence: 99%